1998
DOI: 10.1016/s0735-1097(98)00428-8
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced secretion of insulin plays a role in the development of atherosclerosis and restenosis of coronary arteries: elective percutaneous transluminal coronary angioplasty in patients with effort angina

Abstract: Enhanced secretion of insulin during the OGTT might be useful as a predictor of coronary atherosclerosis and of restenosis after elective PTCA in nondiabetic patients with effort angina.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 35 publications
1
19
0
Order By: Relevance
“…Additionally, endothelial dysfunction as an effect of insulin therapy might be responsible for accelerated atherosclerosis in untreated lesions or enhanced restenosis in treated lesions. 10,11 Hyperinsulinemia, which also occurs in insulin-requiring diabetic patients treated with insulin, may contribute to the atherogenic process. Although we did not collect information on the etiology of diabetes in insulin-treated patients in the Dynamic Registry, it is likely that the vast majority of patients were likely to have type 2, insulinresistant, diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, endothelial dysfunction as an effect of insulin therapy might be responsible for accelerated atherosclerosis in untreated lesions or enhanced restenosis in treated lesions. 10,11 Hyperinsulinemia, which also occurs in insulin-requiring diabetic patients treated with insulin, may contribute to the atherogenic process. Although we did not collect information on the etiology of diabetes in insulin-treated patients in the Dynamic Registry, it is likely that the vast majority of patients were likely to have type 2, insulinresistant, diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…There is no clear evidence that increased insulin or other physiologicaal changes associated with insulin resistance are individually linked to these changes, although this has been suggested by some human studies (34,40), nor is the role of hyperglycemia fully understood. Whereas other investigators have suggested that diabetic patients have an impaired response to NO and that this impairment in NO production can increase inflammation following injury (18,54,56), our study does not suggest or prove that the primary insult in DM is decreased NO bioavailability.…”
Section: Discussionmentioning
confidence: 99%
“…46 Long-term cardiovascular events are often caused by disease progression at sites not treated with stents. Progression of disease was highlighted in the experience of the group from Toulouse, France.…”
Section: Should Drug-eluting Stents Change the Selection For Revasculmentioning
confidence: 99%